The Correlation between Self Efficacy and Self Directed Learning Readiness among Students of Medical Faculty Sebelas Maret University - Kartika Yuliana Putri; Ratna Kusumawati; Amandha Boy Timor Randita (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: The students of medical faculty are expected to have self directed learning (SDL) skill. SDL measured by indicatorself directed learning readiness (SDLR).The implementation of SDLis influenced by internal and external factor should run in balance. Self efficacy is an internal factor which influencing SDL. The aim of the research was to investigate the correlation between self efficacy and SDLR among students of Medical Faculty Sebelas Maret University. Methods: This research was a cross sectional observational analytic. We were conducted at Medical Faculty Sebelas Maret University in October 2015. Data was collected by using stratified random sampling to 276 samples of students. SDLR was measured by Self Directed Learning Readiness Scale for Nursing Education (SDLRS-NE) and self efficacy was measured by General Self Efficacy Scale (GSES). Both of them have been tested for validity and reliability. Correlation nonparametric Spearman test was used to analyse the data. Results: Results were revealed significant correlation (p = 0.000) between the variables. Moderate relationship (r = 0.572) was found between students self-efficacy and SDLR in the Medical Faculty Sebelas Maret University. Conclusions: Self efficacy was found positively correlated with SDLR students of Medical Faculty Sebelas Maret University. Keywords: Self efficacy, Self Directed Learning Readiness